Soil organic carbon and ecosystem multifunctionality are enhanced by subsoiling in fluvo-aquic soil of North China Plain - Wang, Mengru; Wang, Renzhuo; Jiang, Guiying; Li, Yueying; Liu, Chaolin; Yang, Jin; Jie, Xiaolei; Shen, Fengmin; Liu, Fang; Liu, Shiliang (Frontiers in Plant Science, 2025)
This study investigated the impact of various tillage modes on soil carbon (C) components, crop yield, enzyme activity, and ecosystem multifunctionality (EMF) in the North China Plain (NCP), aiming to determine the most effective tillage practice for C sequestration in the region. Field experiments were conducted from 2016 using a split-plot design that included rotary tillage (RT) and deep tillage (DT) during the wheat season and no-tillage (NT), subsoiling in-row (SIR), and subsoiling inter-row (SBR) during the maize season. Related tillage modes based on the total amount of straw returned. Soil bulk density (BD), soil C components, soil organic carbon (SOC) storage, enzyme activities, soil quality index (SQI), EMF, and wheat yield were measured and analyzed. Compared to rotary tillage-no-tillage (RT-NT), the BD of the 0–40 cm soil layer decreased under the other treatments during 2018–2019. The C component content decreased with soil depth across all treatments. Treatments incorporating subsoiling during the maize season led to higher SOC, labile organic carbon (LOC), non-LOC, and microbial biomass carbon (MBC) in the 20–40 cm soil layer. DT-SBR and DT-SIR increased SOC storage. Enzyme activities were highest in the 0–20 cm soil layer under RT-SBR and RT-SIR, while in the 20–40 cm soil layer, enzyme activity peaked under DT-SBR and DT-SIR. The highest SQI value in the 0–20 cm layer was observed under RT-SBR and RT-SIR in both years. Meanwhile, the highest EMF values were under DT-SIR and DT-SBR in the 30–40 cm layer in 2018, ranged from −0.79 to −0.08. Key factors influencing EMF included MBC, LOC, SOC, and dissolved organic carbon (DOC), with EMF showing a strong positive correlation with SQI. Subsoiling during the maize season enhanced wheat yield, with the highest values for RT and DT being 6697 and 6587 kg ha-1, respectively. In conclusion, DT during the wheat season and subsoiling during the maize season promoted the transformation of SOC, enhanced yield, enzyme activity, SQI, and EMF. These benefits contributed to greater C sequestration in deeper soil layers, offering a sustainable approach to soil management in the fluvo-aquic soils of the NPC.